Fitness and wellness - Hoeger, Werner W.K.; Hoeger, Sharon A.; Fawson, Amber Lee; Hoeger, Cherie I. (Boston, MA Cengage Learning, Inc., 2017)
As you study this book and complete the respective activities, you will learn to do the following: Understand the importance of good physical fitness and a wellness lifestyle in the achievement of good health and quality of life and a more productive and longer life; Determine whether medical clearance is needed for your safe participation in exercise; Learn behavior modification techniques to help you adhere to a lifetime fitness and wellness program; Assess the health-related components of fitness (cardiorespiratory endurance, muscular fitness [strength and endurance] muscular flexibility, and body composition); Write exercise prescriptions for cardiorespiratory endurance, muscular fitness, and muscular flexibility; Analyze your diet and learn the principles that govern sound nutrition; Develop sound diet and weight-management programs; Understand stress, lessen your vulnerability to stress, and implement a stress management program if necessary; Implement a cardiovascular disease risk-reduction program; Follow guidelines to reduce your personal risk of developing cancer; Implement a smoking cessation program, if applicable; Understand the health consequences of chemical dependency and irresponsible sexual behaviors and learn guidelines for preventing sexually transmitted infections; Discern between myths and facts of exercise and health-related concepts.
Chapter 1. Introduction to physical fitness and wellness -- Chapter 2. Assessment of physical fitness -- Chapter 3. Exercise prescription -- Chapter 4. Evaluation fitness activities -- Chapter 5. Nutrition for wellness -- Chapter 6. Weight management -- Chapter 7. Stress management -- Chapter 8. A Healthy lifestyle approach -- Chapter 9. Relevant fitness and wellness issues
Keywords: Health; Physical fitness